PROFIL KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTs BERKEMAMPUAN MATEMATIKA TINGGI PADA MATERI BARISAN DAN DERET ARITMETIKA - Subhi, Muhammad Ari; Setiaji, Ade Eky (Universitas Islam Nusantara, 2024)
The ability to solve mathematical problems is crucial for students as it can spark curiosity, enhance the application of scientific knowledge, and encourage students to utilize all their abilities in solving everyday problems. This research is a descriptive qualitative study that aims to present the profile of the mathematical problem-solving abilities of high-achieving mathematics students at the MTs (Islamic Junior High School) level in the topic of Arithmetic Sequences and Series. The subjects of this study were two high-achieving mathematics students from the eighth grade at MTs during the second semester of the 2023/2024 academic year. The selection of subjects was based on assessment results from the previous semester. The data collection techniques used in this study were written tests, interviews, and documentation. The data analysis technique employed was interpretive analysis. The data analysis was based on Polya's problem-solving process framework. The research findings revealed that high-achieving mathematics students met the problem-solving process through the phases of understanding the problem, devising a plan, and carrying out the plan. However, high-achieving students did not fully meet the problem-solving process through the looking back phase. Therefore, special attention is needed to guide students to become accustomed to revisiting and checking their solutions when solving mathematical problems.